Green Marketing of Analysis: Branding, Positioning and Eco-Friendly Products (Literature Review) - Teguh Maianto; Lily Yuntina; Sri Yanthy Yosepha; Kamsariaty Kamsariaty; Bambang Wijanarko (Greenation Research & Yayasan Global Resarch National, 2024)
Literature review research on green marketing analysis: branding, positioning and environmentally friendly products is a scientific literature article in the scope of marketing management science. The purpose of this literature research is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The approach used in this study is descriptive qualitative. The data collection technique uses literature studies. The data used in this descriptive qualitative approach comes from previous research that is relevant to this study and is sourced from academic online media such as the Scopus Emerald Journal, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. The results of this literature review article are: 1) Branding has an effect on green marketing; 2) Positioning has an effect on green marketing; and 3) Environmentally friendly products have an effect on green marketing.